(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article examines the legislative regulation of the legal status of foreign persons in procedural legislation, in particular, issues of arbitration courts and the execution of foreign decisions in the Republic of Uzbekistan. It is concluded that all changes and additions made to the procedural legislation ensure equality of participants in the process and facilitate interaction between countries in the field of legal assistance, strengthening legal guarantees for foreign persons participating in legal disputes on the territory of Uzbekistan.